PERMODELAN KEBUTUHAN TRANSPORTASI MASSAL GUIDED BUSWAY MENGGUNAKAN STRUCTURAL EQUATION MODELING - Supriyatno, Dadang; Sulistio, Harnen; Djakfar, Ludfi; Wicaksono, Achmad (Jurnal Transportasi, 2012)
Transportation problem is complex because the growth of road infrastructure is not proportional to the increase in the number of travels. This is indicated by the increasing levels of private vehicle ownership, numer of trips, insufficient of public transport services, and limited road infrastructure. In this study, the pattern of mass transit, as stated in Law No. 22 of 2009, was examined. Analyses were performed using Confirmatory Factor Analysis and Structural Equation Modeling. The results showed that the variables of Travel Origin and Destination, Travel Patterns, Willingness, and Ability to Pay explained approximately77.0% of the variation in the Guided Busway Needs variable. In addition, Travel Origin and Destination, Travel Patterns, and Willingness and Ability to Pay have positive and significant impact on the Guided Busway Needs.Keywords: mass transit, guided busway, origin destination travel, travel patterns, willingness and ability topay.